The Taiji Tennis Method: Using Taiji Basics to Enhance Performance and Power in Western Tennis Players - Dokken, John (The Journal of the International Society of Chinese Health Practices, 2024)
World champion Novak Djokovic practices Taijichuan (Tai Chi Chuan) and meditation as part of his daily training and on-court routine, thus supporting the idea that Taijichuan can enhance tennis performance. Former University of Virginia head mens tennis coach John Dokken developed the Taiji Tennis Method (TTM) approximately 30 years ago (when Novak was still a young child) after he learned both Taijichaun and QiGong from his friend and business partner John Alton. While coaching and playing tennis, Dokken began applying the Taiji principles of relaxed , efficient movement to his own performance in regional and national playing competitions, as well as to that of his student athletes. Over the years of testing and applying Taiji principles, The TTM became the systematized approach outlined in the presentation. It illustrates basic Taiji movements that are most applicable to tennis physics and kinesiology, and cites case studies that demonstrate the efficacy and value of TTM. A few cases go beyond the mere physical aspects of the TTM and explore the possibilities of incorporating aspects of Qigong that sharpens the players awareness and anticipation of opponent on-court behavior and attitude. The TTM shows that creative integration of Taijiquan and Qigong into Western sports such as tennis benefits players and enhances appreciation of traditional Chinese health practices.